La pernice bianca Lagopus mutus helveticus (Thienemann, 1829) nel Parco Naturale delle Prealpi Giulie: stime della distribuzione e della consistenza della popolazione - De Luca M.; Strazzaboschi L.; Ciani L.; Pizzul E. (2017)
Abstract - In this study we report the results relevant to monitoring of ptarmigans Lagopus mutus helveticus (Thienemann, 1829) in the Julian Prealps Natural Park. The data we have collected have allowed us to establish their distribution, evaluate the extent of their presence and locate the areas whitin the Park which have the most significant role for conservation purposes. We also report some environmental information about the locations selected by ptarmigans. The species is present in the eastern part of the area, though unevenly; we estimate the presence of 16 (11-18) territorial males in spring; in our study area the density of territorial males was 1,83/Km2. We did not spot any territorial males below 1900 metres a.s.l. A suitability model was generated using distribution data, in order to develop a potential distribution of suitable area for the species within the Park. The eastern portion of the protected area proves to be more relevant to the conservation of the species.